Robust Distributed Source Coding - Jun Chen; Berger, T. (IEEE transactions on information theory, 2008)
We consider a distributed source coding system in which several observations must be encoded separately and communicated to the decoder by using limited transmission rate. We introduce a robust distributed coding scheme which flexibly trades off between system robustness and compression efficiency. The optimality of this coding scheme is proved for various special cases.